Potential of local Bacillus spp. isolates as wilt disease biocontrol agents for Fusarium oxysporum f. sp. cepae on Allium x wakegi - ASRUL ASRUL (Society for Indonesian Biodiversity, 2023)
Abstract. Asrul. 2023. Potential of local Bacillus spp. isolates as wilt disease biocontrol agents for Fusarium oxysporum f. sp. cepae on Allium x wakegi. Biodiversitas 24: 4989-4997. Implementation of biological agents for eradication and inhibition of plant pathogens is often ineffective due to its protracted consequences. The objective of this research was to examine the potential of local isolates of Bacillus spp. as a biocontrol agent in suppressing Fusarium wilt disease (Fusarium oxysporum f. sp. cepae) on wakegi onions (Allium × wakegi Araki). The research was conducted in a completely randomized design (CRD) with the treatment of rhizospheric bacterial isolates. The treatments included control (without isolate application) and seven bacterial isolates, namely KP17, KP5, DB9, DB12, DB18, DG4 and DG11. Each treatment was repeated five times and each replication consisted of 10 wakegi onion plants. The results showed that a total of 46 isolates were isolated from the rhizosphere of wakegi onion and seven isolates among them were selected as biocontrol agents. These isolates had similarities with Bacillus spp. in accordance with the colony morphology, physiology and biochemical characteristics. Among the isolates found, DB12 emerged as the isolate that had the potential to be developed as a biocontrol agent.